2013
DOI: 10.1155/2013/257942
|View full text |Cite
|
Sign up to set email alerts
|

Are Both Ultrasonography and Mammography Necessary for Cancer Investigation of Breast Lumps in Resource-Limited Countries?

Abstract: Objective. To reevaluate the diagnostic value of breast imaging in the diagnosis of breast cancer in areas where health resources are limited. Methods. Patients were women presenting with breast lumps in two university-affiliated tertiary hospitals, Thailand, during 2006 and 2010. Clinical data were abstracted from the breast cancer registration database and patient records. The diagnostic predictive ability of ultrasonography and mammography was obtained from logistic regression analysis and presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…We are not the first to suggest that US could replace mammography in some women, though prior reports are limited to women with symptoms. In 3129 symptomatic women in Thailand, US showed an area under the curve of 0.962, which was better than mammography at 0.954 (P = .015), and adding mammography to US produced statistically insignificant improvement (21). In 1208 focally symptomatic women age 30 to 39 years, Lehman et al (22) found higher sensitivity for US than mammography among the 23 (1.9%) women with cancer, with 22 of 23 (95.6%) cancers seen by US and only 14 of 23 (60.9%) with mammography (P = .0098), albeit with a higher false-positive rate for US.…”
Section: Discussionmentioning
confidence: 92%
“…We are not the first to suggest that US could replace mammography in some women, though prior reports are limited to women with symptoms. In 3129 symptomatic women in Thailand, US showed an area under the curve of 0.962, which was better than mammography at 0.954 (P = .015), and adding mammography to US produced statistically insignificant improvement (21). In 1208 focally symptomatic women age 30 to 39 years, Lehman et al (22) found higher sensitivity for US than mammography among the 23 (1.9%) women with cancer, with 22 of 23 (95.6%) cancers seen by US and only 14 of 23 (60.9%) with mammography (P = .0098), albeit with a higher false-positive rate for US.…”
Section: Discussionmentioning
confidence: 92%
“…In the Japan Strategic Anti‐cancer Randomized Trial, 184 breast cancers were detected in 36 859 participants by ultrasound combined with mammography, of whom 41 were positive in mammography only and 67 were positive in ultrasound only, with the diagnosis rate of breast cancer, therefore being higher for ultrasound than that for mammography 14 . A study from Thailand included 3129 symptomatic women and found that the AUC for ultrasound was 0.962, which was superior to that of mammography at 0.954 ( p = 0.015), implying that ultrasound is more accurate than mammography 27 . An international meta‐analysis showed that when looking at data from low‐ and middle‐income countries alone, breast ultrasound did not have lesser sensitivity and specificity than those of mammography 28 .…”
Section: Discussionmentioning
confidence: 99%
“… 14 A study from Thailand included 3129 symptomatic women and found that the AUC for ultrasound was 0.962, which was superior to that of mammography at 0.954 ( p = 0.015), implying that ultrasound is more accurate than mammography. 27 An international meta‐analysis showed that when looking at data from low‐ and middle‐income countries alone, breast ultrasound did not have lesser sensitivity and specificity than those of mammography. 28 Even in Western countries, ultrasound is no less sensitive and accurate than mammography.…”
Section: Discussionmentioning
confidence: 99%
“…Each BI‐RADS category has a reported likelihood of cancer and a proposed management recommendation. Studies in the literature state that the use of imaging combined with FNAB increased the rate of prediction of malignancies 6,7 …”
Section: Introductionmentioning
confidence: 99%